Las dislalias y su influencia en la ansiedad de los niños de segundo, tercero y cuarto año de educación básica que asisten a la escuela vespertina Lauro Damerval Ayora de la ciudad de Loja, periodo 2013- 2014 - Roman Pogo, Paulina Elizabeth (2014)
This research entitled: The Dyslalias and its influence on the anxiety of the children of second, third and fourth year of basic education who attend evening school Lauro Damerval Ayora from the city of Loja, 2013-2014 period. It had as general objective: to determine how influences the dyslalia anxiety with second, third and fourth year of basic education. The main methods used to carry out this investigation were: scientific, descriptive, analytic - synthetic, inductive. The techniques used were: survey and questionnaire of child anxiety (CAS) that allowed meet and gather information on the levels of anxiety of the students and the joint Test repetition aimed to find the phoneme that causes greater difficulty of articulating to the students. After having done the research could come to the following conclusions: it was able to identify that the students had greater difficulty to articulate the phonemes/r /, / y /, / bra /, / pre /, / iu /. Most of the students have a level of mild anxiety when they are against strangers are sociable and interested by strike up a conversation. Finally it presents guidelines for proposal in order to improve and correct the dyslalia of students in second, third and fourth year of basic education of the educational unit Lauro Damerval Ayora.